Spinal epidural abscess treated with antibiotics alone. (30th April 2013) - Pathak, Ashish; Singh, Poonam; Gehlot, Prateek; Dhaneria, Mamta
Abstract : Spinal epidural abscess (SEA) is a rare clinical condition among children. Most patients do not present with classical signs. A 13-year-old boy without any predisposing factors presented with paraparesis, bladder and bowel involvement. MRI spine demonstrated an SEA at the C7 and D1 levels on both sides of the midline with cord oedema at the C2–3 to C6 level with minimal marrow oedema in the C6 vertebral body. We treated the patient with antibiotics (ceftriaxone and vancomycin) alone. The patient showed excellent response with only minimal residual gait disturbance at the end of 6 weeks of antibiotic therapy. This is the first paediatric report of complete recovery of a patient at clinical stage 4 following antibiotic treatment alone from India. However, caution should be exercised to closely monitor the patient's recovery as any progression in the neurological state warrants surgery.